Further conventions for NMR shielding and chemical shifts (IUPAC Recommendations 2008) - Harris, Robin K.; Becker, Edwin D.; Cabral de Menezes, Sonia M.; Granger, Pierre; Hoffman, Roy E.; Zilm, Kurt W. (Pure and applied chemistry, 2008)
IUPAC has published a number of recommendations regarding the reporting of nuclear magnetic resonance (NMR) data, especially chemical shifts. The most recent publication [ , 1795 (2001)] recommended that tetramethylsilane (TMS) serve as a universal reference for reporting the shifts of all nuclides, but it deferred recommendations for several aspects of this subject. This document first examines the extent to which the H shielding in TMS itself is subject to change by variation in temperature, concentration, and solvent. On the basis of recently published results, it has been established that the shielding of TMS in solution [along with that of sodium-3-(trimethylsilyl)propanesulfonate, DSS, often used as a reference for aqueous solutions] varies only slightly with temperature but is subject to solvent perturbations of a few tenths of a parts per million (ppm). Recommendations are given for reporting chemical shifts under most routine experimental conditions and for quantifying effects of temperature and solvent variation, including the use of magnetic susceptibility corrections and of magic-angle spinning (MAS). This document provides the first IUPAC recommendations for referencing and reporting chemical shifts in solids, based on high-resolution MAS studies. Procedures are given for relating C NMR chemical shifts in solids to the scales used for high-resolution studies in the liquid phase. The notation and terminology used for describing chemical shift and shielding tensors in solids is reviewed in some detail, and recommendations are given for best practice.